2020
DOI: 10.1037/edu0000453
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mathematical word problem solving interventions for students with learning disabilities and/or mathematics difficulties: A meta-analysis.

Abstract: This meta-analysis synthesized the available empirical evidence on the impact of interventions on the development and enhancement of mathematical word problem solving skills for K-12 students with learning disabilities (LD) and those with mathematics difficulties (MD). A total of 33 studies met inclusion criteria for this meta-analysis. After removing 2 influential data points, 31 true-experimental or quasi-experimental studies (34 independent effect sizes) contributed effect sizes for this meta-analysis. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
71
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(90 citation statements)
references
References 78 publications
(123 reference statements)
10
71
4
Order By: Relevance
“…Results showed that researcher‐developed measures had higher effects than standardized tests, a finding that contradicts Jitendra et al.’s (2018) conclusion. Yet our finding is consistent with Jitendra et al.’s (2020) observation, and with other researchers' findings (e.g., Lein et al., 2020). Researcher‐developed assessments are more closely aligned with instructional programs within interventions (Scammacca et al., 2007), and thus, have a higher sensitivity to changes in students' performance than standardized tests (Deno, 2003; Marston & Magnusson, 1985).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Results showed that researcher‐developed measures had higher effects than standardized tests, a finding that contradicts Jitendra et al.’s (2018) conclusion. Yet our finding is consistent with Jitendra et al.’s (2020) observation, and with other researchers' findings (e.g., Lein et al., 2020). Researcher‐developed assessments are more closely aligned with instructional programs within interventions (Scammacca et al., 2007), and thus, have a higher sensitivity to changes in students' performance than standardized tests (Deno, 2003; Marston & Magnusson, 1985).…”
Section: Discussionsupporting
confidence: 94%
“…Moderator Levels and Operational Definitions Intervention characteristics Content domain a We consulted the CCSS-M (National Governors Association Center for Best Practices & Council of Chief State School Officers, 2010) and National Council of Teachers of Mathematics (NTCM, 2000) standards for the content areas students must master to become proficient in mathematics and coded measures as (a) numbers and operations, (b) fractions, (c) ratios & proportions, (d) geometry, (e) algebra, (f) measurement and data, and (e) multiple content domains a Intervention model bFollowing previous research(Lein et al, 2020;Maccini et al, 2007;Myers et al, 2015) we grouped studies as (a) TBI= used computer-assisted instruction and video disc-based instruction (e.g., EAI); (b) CBI = used cognitive or meta-cognitive techniques, such as reasoning strategies, self-monitoring strategies (e.g., think-aloud), or mnemonic devices to solve problems; (c) SBI = included schema-based or schema-broadening (and transfer) instruction (Jitendra et al, 2017a,b); (d) VR = used concrete (e.g., manipulatives), semiconcrete (e.g., pictures and diagrams), or abstract (e.g., symbols) representations to learn concepts; (e) other intervention models = intervention fell outside of the preceding four categories Instructional setting (a) General education settings only = occurred exclusively in general education classrooms; (b) other instructional settings = occurred in locations outside the general education classroom, such as resource rooms, or in a combination of general education and other alternate classroom settings Interventionist (a) Teachers only = general or special education teacher provide instruction; (b) researcher-involved = Instruction provided by researcher, graduate research assistant, or researchers and teachers jointly); (c) other Interventionists (e.g., computers, tutors, and volunteers) Intervention length c (a) Short term (i.e., ≤7 sessions); (b) intermediate term (i.e., 8-30 sessions); (c) long term (> 30 sessions). Group size (a) Small group ≤ 8 students; (b) large group ≥ 8 students (Stevens et al 2018) Sample composition (a) Majority students with LD in math ≥ 50% of the total sample had documented Math LD; (b) majority not students with LD in math ≥ 50% of the total sample did not have documented Math LD Study design characteristics Study quality (a) High quality (HQ) = met at least 9 of the 10 essential quality indicators and at least 4 of the 8 desirable quality indicators; (b) acceptable quality (AQ) = met at least 9 of the 10 essential quality indicators and at least 1 of the 8 desirable indicators; (c) low quality = met none of these criteria.…”
mentioning
confidence: 95%
“…The usage of schema whenever possible is underlined by Lein et al [49], who proved that "intervention effects for schema-based transfer instruction were larger than those for schema-based instruction", illustrating that mathematical word-problem-solving interventions are suitable for students with learning disabilities and/or mathematics difficulties as well.…”
Section: Step 3 Executing the Planmentioning
confidence: 99%
“…For instance, children's magnitude knowledge can be improved by playing linear board games (Siegler & Ramani, 2009), and children's understanding of arithmetic principles can be enhanced by practicing relevant arithmetic problems that are blocked together (e.g., presenting 6 + 3 immediately after 3 + 6; Canobi, 2009). Furthermore, children's mathematical problem‐solving performance can be improved using schema‐based instructions (Lein et al, 2020) in which students are taught to classify mathematical problems based on their problem types (Powell, 2011). While all these interventions are effective in improving children's mathematical competence, their relatively narrow foci might limit their effectiveness.…”
Section: The Next Step: Examining the Unique Roles Of The Three Compomentioning
confidence: 99%